What are the clinical and radiological characteristics of spinal injuries from physical abuse: a systematic review. Issue 5 (27th November 2009) - Kemp, A M; Joshi, A H; Mann, M; Tempest, V; Liu, A; Holden, S; Maguire, S
Abstract : Aim: Systematic review of 'What are the clinical and radiological characteristics of inflicted spinal injury?' Methods: Literature search of 20 electronic databases, websites, references and bibliographies (1950–2009) using selected keywords. Critical appraisal: by two trained reviewers, (a third review, if discrepant). Inclusion criteria: primary studies of inflicted spinal injury in children <18 years, alive at presentation, with a high surety of diagnosis of abuse and sufficient detail to analyse. Results: 19 studies of 25 children were included. Twelve children (median age 5 months) had cervical injury. In seven cases, the clinical signs of spinal injury were masked by respiratory symptoms and impaired levels of consciousness; six of these children had coexistent inflicted head trauma. Twelve children had thoraco-lumbar injury (median age 13.5 months), 10/12 had lesions at T11–L2, and 9/12 had fracture dislocations. All children had focal signs: 10/12 had lumbar kyphosis or thoraco-lumbar swelling, and two had focal neurology. One child had cervical, thoracic and sacral injuries. Conclusions: Spinal injury is a potentially devastating inflicted injury in infants and young children. The published evidence base is limited. However, this case series leads us to recommend that any clinical or radiological indication of spinal injury warrants an MRI. In children undergoing brain MRI for abusive head trauma, consideration should be given to including an MRI of the spine. All skeletal surveys in children with suspected abuse should include lateral views of the cervical and thoraco-lumbar spine. Further prospective comparative studies would define the discriminating features of inflicted spinal injuries.